Changing the manner of electing the President of the Republic of Kosovo - Susuri, Driola; Kryeziu, Kadri (Technium Social Sciences Journal, 2021)
The Constitution of the Republic of Kosovo in its basic provisions has constituted the principle of separation and control of the balance between state powers as a fundamental principle of democracy, by designating representative bodies belonging to state powers such as Parliament, Government, and Judiciary. In addition, the Constitution sanctions other state bodies that have a constitutional character and together create the form of governance in the Republic of Kosovo. Among them also the President functions as a constitutional body exercising the executive duty and having ceremonial competencies. The President in Kosovo is a neutral authority because he/she is a representative of the people’s unity. The authorities in Kosovo create a "check and balance" among themselves for the normal functioning of the state. Kosovo is considered a parliamentary Republic, not sanctioned by the constitution but implied based on the decision of the Parliament of the Republic of Kosovo.In addition to electing the Government, the Parliament also elects the President of the Republic, so in this study, we will address the function of the President, the exercise of his duties, his competencies, and his relationship with other state bodies. We will also analyze the system of governance and the principle of separation and balance of powers, with special emphasis on the constitutional position of the President in the Republic of Kosovo. Among other things, we will address in particular the complexity of the procedures for the election of the President of the Republic of Kosovo. Considering the ongoing problems that have accompanied the presidential elections in the Republic of Kosovo and that continue to be so, it is necessary to clarify whether “the constitutional reform initiative for the President of the Republic of Kosovo to be voted by the people is considered the most current and best way of overcoming the present parliamentary stalemate in the election of the candidate for the President of the Republic, as well as whether the implementation of this reform is conditioned by the will of the political parties and the people”. In general, from the stated scientific elaboration of the topic, we can conclude that the intention of this paper consists in determining the constitutional regulation of the institution of the President of the Republic of Kosovo applied in the parliamentary system, empirical elaboration of problems that accompanied the election of presidents in the Republic of Kosovo as well as the immediate need to change the manner of electing the President of the Republic of Kosovo.